TRANSFORMASI ILMU DILALAH DAN ILMU MU'JAM DALAM LINGUISTIK ARAB: ANALISIS KRITIS PENDEKATAN KLASIK DAN KONTEMPORER DALAM PERSPEKTIF HISTORIS - Reni Dwita Putri; Lilis Suryani; Nurjannah Harahap; Husnatul Hamidiyyah; Riko Andrian (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the historical development of Ilm al-Dilālah (semantics) and Ilm al-Mu'jam (lexicography) within the Arabic linguistic tradition, and to identify the epistemological relationship between the two disciplines from the classical to the contemporary era. A qualitative method with a historical-analytical-comparative approach was employed through library research. Data were collected from primary sources comprising classical Arabic linguistic texts and secondary sources including relevant academic journals and books, then analyzed using a descriptive-analytical method. The findings reveal that Ilm al-Dilālah evolved from meaning analysis rooted in the need to understand sacred texts during the classical era into a multidisciplinary field encompassing cognitive, computational, and neuro-semantics in the contemporary period. Meanwhile, Ilm al-Mu'jam developed from phonetics-based and root-based lexicographic systems in its early stages, through root-based classical dictionaries, to alphabetical and digital systems in the modern era, including its development in Indonesia through Arabic-Malay to multilingual digital dictionaries. This study concludes that Ilm al-Dilālah and Ilm al-Mu'jam share a close epistemological relationship: semantic theory of meaning provides the theoretical foundation for definitional systems in lexicography, making both disciplines mutually complementary as central pillars in the preservation, comprehension, and development of the Arabic language.